Analisis Kekerabatan Tanaman Famili Fabaceae Berdasarkan Karakteristik Morfologi di Kecamatan Jatinangor, Kabupaten Sumedang - Salma Rahmah; Sandy Setiawan (International Forum of Researchers and Lecturers, 2023)
Indonesia is a country with very high biodiversity both in flora and fauna groups so that Indonesia is nicknamed the